2021
DOI: 10.3390/foods10123103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age of Agave tequilana Weber Blue Variety on Quality and Authenticity Parameters for the Tequila 100% Agave Silver Class: Evaluation at the Industrial Scale Level

Abstract: Due to the oversupply and scarcity cycles of the Agave tequilana Weber blue variety, the effect of agave age (harvested in 4, 5, and 6 years) as raw material for the tequila 100% agave silver class was studied for each stage in a full-scale (industrial) process. Harvested plants showed differences in their morphological characteristics that affected the amount of juice; this had an impact in the fermentation stage since must composition was modified in the nitrogen content and juice/exudate ratio. This was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Consequently, these compounds have higher values in their variation coefficients (>20%), and this effect its related to Tequila 100% agave production processes. It is proposed that these variations could be due to the fermentation and distillation stages, due to the fact that each company possesses yeast strains and specific operational parameters to grant unique organoleptic properties to their products [ 32 , 33 , 34 , 35 , 36 , 37 ]. These differences can also be observed when comparing the values of Tequila against alcoholic beverages produced from other agave species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, these compounds have higher values in their variation coefficients (>20%), and this effect its related to Tequila 100% agave production processes. It is proposed that these variations could be due to the fermentation and distillation stages, due to the fact that each company possesses yeast strains and specific operational parameters to grant unique organoleptic properties to their products [ 32 , 33 , 34 , 35 , 36 , 37 ]. These differences can also be observed when comparing the values of Tequila against alcoholic beverages produced from other agave species.…”
Section: Resultsmentioning
confidence: 99%
“…The proposal for the δ 13 C VPDB values is more negative in this congener due to the operating conditions in the fermentation stage. It has been evidenced that several operation conditions can affect the physicochemical profile of the beverages, such as pH, temperature, nutrients, and kind of yeast [ 11 , 32 , 42 , 44 ]; among them, the type of yeast stands out, which has been shown to be the one that has the most influence in producing this congener [ 45 ]. In such a way, the production of ethyl acetate can be related due to the type of yeast and plants used, due to the fact that there is a complex amount of nutrients that enhance fermentation according to its concentration, such as sugars, amino acids, fatty acids, and micronutrients, which impact the fermentation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tequila industry seeks to meet the sustained growth in demand for tequila without transferring the benefits of this increased income to the primary producers of agave. From this perspective, we can understand the significance of the "historical moment" that saw the publication of the investigation "Effect of the age of the tequilana agave Weber Blue Variety on the quality and authenticity parameters for 100% Agave Silver Class tequila: Industrial scale evaluation" (Acosta Salazar et al, 2021) that demonstrated that processing "young agave" plants, just 3 or 4 years old (previously 6 years), does not affect its usefulness. This shift to the use of young agave does not entail any economic benefit for the primary producer 32 either (the cultivation cycle of the blue agave plant from planting to harvesting is reduced by up to 50%, and therefore so are farmers' costs), but does contribute significantly to the increase in its supply, further depressing its value.…”
Section: Discussionmentioning
confidence: 99%
“…Acosta Salazar et al (2021) describes the severe problems suffered by the supply chain of the tequila production process as a result of the length of time the agave plant takes to reach maturity and be ready for use (six years). He points out that "the transition between scarcity and oversupply" has been a cyclical driver of falls or steep increases in its value.…”
Section: Introductionmentioning
confidence: 99%